Perilaku dan Persepsi Keyakinan Ibu Hamil Terhadap Screening HIV di Kota Pematangsiantar - Dame Evalina Simangunsong; Kandace Sianipar; Juliani Purba (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Prevention of HIV transmission from mother to baby or Prevention of Mother to Child Transmission (PMTCT) is an effective and in achieving a broad objective in suppressing maternal and infant mortality related to the level of public health in a region.Public Health Center with VCT service in the city Pematangsiantar has not yet fully provide PMTCT to realize pregnant women for screening HIV/AIDS. Pregnant women with HIV/AIDS still have a loss to follow up, this is a threat to suppress the prevalence and incidence of HIV/AIDS. Obstetrics study Program which also integrates the promotion of HIV/AIDS and IMS into KIA service to be responsible in suppressing its spread. These research identified the behavior and perception of pregnant women's beliefs against HIV screening to determine the level of consciousness in conducted HIV screening. These research was a descriptive studied with cross sectional design. Pregnant women who were netted in the ANC Ministry were the populations in this study. Data analysis was conducted to see the behavior and perception of pregnant women's beliefs against HIV screening. Data processed with univariate analysis. Found 337 expectant mothers who perform ANC and as many as 194 people were not willing to do HIV screening. Found low-level, disagreement and low-action and low-confidence perception of HIV screening.It is necessary to conduct a strategy approach with personal counseling, peer-education and home visits in the net of pregnant women with HIV. Keywords: behavior; HIV; screening; perception ABSTRAK Pencegahan penularan HIV dari ibu ke bayinya atau Prevention of Mother to Child Transmission (PMTCT) adalah suatu cara yang efektif dan dalam mencapai tujuan yang luas dalam menekan angka kematian ibu dan bayi yang berkaitan dengan tingkat kesehatan masyarakat di suatu wilayah. Puskesmas dengan layanan VCT di kota Pematangsiantar belum sepenuhnya memberikan PMTCT untuk menyadarkan ibu hamil untuk screening HIV/AIDS. Ibu hamil dengan HIV/AIDS masih ada yang loss to follow up, hal ini menjadi ancaman dalam menekan prevalensi dan insiden HIV/AIDS. Program Studi Kebidanan Pematangsiantar yang turut mengintegrasikan Promosi HIV/AIDS dan IMS ke dalam pelayanan KIA ikut bertanggungjawab dalam menekan penyebarannya. Penelitian ini mengidentifikasi perilaku dan persepsi keyakinan ibu hamil terhadap screening HIV untuk mengetahui tingkat kesadarannya dalam melakukan screening HIV. Penelitian ini merupakan penelitian deskriptif dengan desain cross sectional. Ibu hamil yang terjaring dalam pelayanan ANCadalah populasi dalam penelitian ini. Analisis data dilakukan untuk melihat perilaku dan persepsi keyakinan ibu hamil terhadap screening HIV. Data diolah dengan analisis univariate. Ditemukan 337 ibu hamil yang melakukan ANC dan sebanyak 194 orang belum bersedia dilakukan screening HIV. Ditemukan pegetahuan yang rendah, sikap tidak setuju dan tindakan yang rendah serta persepsi keyakinan yang rendah terhadap screening HIV.Perlu melakukan strategi pendekatan dengan konseling pribadi, peer-edukasi dan kunjungan rumah dalam menjaring ibu hamil dengan HIV. Kata kunci: perilaku; HIV; screening; persepsi